Efficient Transfer Doping of Carbon Nanotube Forests by MoO3 - Yuzheng Guo (ACS Nano, 2015)
We dope nanotube forests using evaporated MoO3 and observe the forest resistivity to decrease by 2 orders of magnitude, reaching values as low as ∼5 × 10–5 Ωcm, thus approaching that of copper. Using in situ photoemission spectroscopy, we determine the minimum necessary MoO3 thickness to dope a forest and study the underlying doping mechanism. Homogenous coating and tube compaction emerge as key factors for decreasing the forest resistivity. When all nanotubes are fully coated with MoO3 and packed, conduction channels are created both inside the nanotubes and on the outside oxide layer. This is supported by density functional theory calculations, which show a shift of the Fermi energy of the nanotubes and the conversion of the oxide into a layer of metallic character. MoO3 doping removes the need for chirality control during nanotube growth and represents a step forward toward the use of forests in next-generation electronics and in power cables or conductive polymers.